Interaksi Kelompok Etnis Tionghoa dengan Etnis Non-Tionghoa Dalam Perguruan Tinggi Negeri: Studi Tentang Pemilihan Institusi oleh Mahasiswa Etnis Tionghoa - Tjen Jocelyn Ivana; Tandiyo Pradekso; S. Rouli Manalu (Interaksi Online, 2023)
Indonesia has a diversity of ethnic groups, one of which is Chinese. Although people of Chinese descent in Indonesia are Indonesian citizens, the sentiment towards ethnic Chinese can still be felt today. This study aims to understand the background of the choice of institutions made by ethnic Chinese students to continue their studies in college and understand the experience of interaction of ethnic Chinese students in higher education. This research is a qualitative study with Jonathan A. Smith's Interpretative Phenomenological Analysis (IPA) analysis method which categorizes research results into reading and re-reading, Initial noting, developing emergent themes, searching for connections across emergent themes, and moving the next cases. The main theory used is Co-Culture Theory. The results of this study are (1) the suspicion of other ethnicities is passed down from one generation to another, (2) the suspicion that will be ostracized by non-Chinese ethnicities makes ethnic Chinese choose to continue their studies at private universities.